Deflection control for piezoelectric actuator through voltage signal and it's application in micromanipulation. (October 2015) - Jain, R.K.; Majumder, S.; Ghosh, Bhaskar; Saha, Surajit
Abstract: Piezoelectric actuator can be used for handling and grasping of miniature parts in micromanipulation where study of stable displacement and force characteristics with voltage are important for developing a micro gripper. In order to obtain these behaviors of piezoelectric actuator, electromechanical characterization of piezoelectric actuator has been carried out in this paper where a mathematical model for deflection and force response of piezoelectric actuator with voltage is derived with the help of a simple first-order model under a step input voltage. This is controlled through a proportional-derivative (PD) controller. Experimentally, it is verified that the piezoelectric actuator attains the maximum deflection upto 1.5 mm and produces force upto 0.203 N by applying voltage (0–60 V). A prototype of novel piezoelectric actuator based micro gripper along with micro manipulation system is developed. By conducting experiments, it is proved that controlled voltage for piezoelectric actuator helps in compensating the misalignment during micro assembly. Highlights: Use of piezoelectric actuator with stable displacement and force characteristics and it's application in micromanipulation. A new design of micro manipulation system with a piezoelectric gripper is proposed. An electromechanical analysis of piezo actuator is carried out where deflection is controlled through PD controller. Demonstration of piezo actuator based micro manipulation system for compensating the misalignment during robotic assembly.